Assessment Of The Follicles in Different Age Groups in Post Mortem Human Ovary (Central Medical College Journal, 2022)
Ovary is one of the essential reproductive organs in human being. A detailed histomorphological feature of ovary is an un-debatable for diagnostic and therapeutic purpose for ovarian disease. The standardization of the morphological and histological measurements of ovary in general in Bangladeshi people is essential to increase the knowledge regarding anatomical variation in our population. So a research work on detailed anatomical parameters of ovary is an un-debatable.Objective: To find out the follicles in different age groups post mortem human ovary.Methodology: The cross-sectional observational study was carried out in the Department of Anatomy, Sylhet MAG Osmani Medical College, Sylhet in collaboration with the Department of Forensic Medicine, Sylhet MAG Osmani Medical College during the period from January 2016 to December 2016. Sixty pairs of human postmortem ovaries were collected. The inclusion criteria were dead bodies autopsied within 36 hours of death. Considerable signs of decomposition or decomposed dead body, presence of gross ovarian disease and any history of poisoning cases were excluded. All the specimens were examined for morphological parameters but only 18 specimens were examined histological parameters.Results: The highest total numbers of the follicles were found in the age group A and lowest total numbers of the follicles were in the age group C. The differences of total numbers of the follicles were significant between group-A and group-B (p